Production of polymalic acid and malic acid from xylose and corncob hydrolysate by a novel Aureobasidium pullulans YJ 6–11 strain. Issue 1 (January 2016) - Zou, Xiang; Yang, Jing; Tian, Xu; Guo, Meijing; Li, Zhenghua; Li, Yunzheng
Graphical abstract: Highlights: A new strain with a high polymalic acid (PMA) yield from xylose was successfully isolated. This strain produced PMA from xylose at a comparable or higher rate than glucose. Different carbon sources produced PMA with a similar molecular weight. The strain can better utilize corncob hydrolysate. Abstract: Polymalic acid (PMA) is a water-soluble biopolymer with many attractive properties for pharmaceutical applications. Its monomer, l -malic acid, is a potential C4 platform chemical, which is widely used in the food industry. In this study, a new strain with a high PMA yield from xylose was isolated and identified as Aureobasidium pullulans based on the morphological and phylogenetic analyzes. This strain produced PMA from xylose at a comparable or higher rate than glucose, and PMA produced from xylose had a similar molecular weight to that produced from glucose. A high final PMA titer of 80.4 g/L (91.2 g/L of malic acid after hydrolysis) was achieved using fed-batch fermentation with xylose in a 5-L fermentor at a PMA productivity of 0.52 g/L h. Corncob hydrolysate could be better utilized producing 28.6 g/L of PMA (or 32.4 g/L malic acid) in batch fermentation. PMA was further characterized for its chemical structure. This strain can be used to produce PMA and malic acid from xylose and lignocellulosic biomass hydrolysates.